Performance Analysis of A Hybrid Mimo Technique for High Rate Wireless Communication System - Kehinde Odeyemi; Erastus Ogunti (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The demand for higher data rate and better quality of service (QoS) in wireless communications was growing fast in the past few years. Obtaining these requirements becomes challenging for wireless communication systems due to the problems of channel multi-path fading, higher power and bandwidth limitations. One of the most promising solutions to this problem is Multiple Input Multiple Output (MIMO) system. This paper proposed a combined spatial multiplexing MIMO scheme with beamforming for high data rate wireless communication. The proposed transmission scheme combines the benefits of both techniques and the system was able to transmit parallel data streams as well as providing beamforming gain. Actually, these diverse techniques, share the same requirement of multiple antenna elements, but differ in the antenna element spacing necessary for the different schemes to work. Thus, smart antenna array was proposed as a possible solution and was adopted at the both transmitter and the receiver. The hybrid technique provides higher spectral efficiency and improve better Bit error rate (BER) of the system than the conventional MIMO, spatial multiplexing and beamforming techniques under the same simulation environment.